Sensitivity pattern of salmonella typhi and paratyphi in paediatric patients - Sohail Ahmad; Rasool, Muhammad Farhan; Kifayatullah; Mansoor Ahmad; Mantasha Raza; Touseef Halim (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the sensitivity patterns of Salmonella typhi and paratyphi in paediatric patients in a public-sector tertiary-care setting. Method: The retrospective, observational study was conducted at Gajju Khan Medical College, Swabi, Pakistan, from January 11 to March 3, 2024, and comprised samples from patients aged 1-14 years who had been confirmed as cases of Salmonella typhi during testing at the Medical Teaching Institution Bacha Khan Medical Complex, Swabi, between January 5 and December 24, 2023. Cultures had been performed manually, while antibiotic susceptibility had been tested using Kirby-Bauer disk diffusion method. Data was analysed using SPSS 25. Results: Of the 63 patients, 40(63.4%) were boys and 23(36.5%) were girls. The overall mean age was 7.8±4.16 years. Among the samples, 6(10.5%) showed sensitivity to ciprofloxacin, while 57(89.4%) exhibited resistance. None of the samples showed sensitivity to ampicillin, and 1(1.5%) was sensitive to ceftriaxone. Azithromycin showed a high sensitivity rate of 60(95.2%). Meropenem and imipenem demonstrated 63(100%) sensitivity. Conclusion: The development of extremely high resistance of salmonella typhi to commonly used antibiotics, such as ampicillin, ciprofloxacin and ceftriaxone show a concerning trend in pediatric patients. Measures need to be taken to prevent the misuse and overuse of antibiotics. Key Words: Enteric fever, Salmonella, Antibiotic sensitivity, Blood culture, Disk-diffusion method, Bauer-Kirby, Azithromycin, Meropenem.